Field measurements reveal local limits of imputed functional traits in tropical trees - Wénita de Souza Justino; Daniel Negreiros; Lara Rodrigues de Andrade; Ilana Zanoni; Miriam Cristina Alvarez Pereira; Simon Pierce; Geraldo Wilson Fernandes (Plant Ecology, 2026)
This study evaluated the reliability of functional data imputed in the classification of ecological strategies according to the CSR model (competitive, stress-tolerant, ruderal) in tree species of a riparian Atlantic Forest in Brazil. Empirical data collected in situ from 68 species were compared with data imputed using the Bayesian Hierarchical Probabilistic Matrix Factorization (BHPMF) technique, considering key functional attributes such as leaf area and specific leaf area. The results showed significant divergences between the classifications based on measured and imputed data, especially for the traits directly involved in the formulation of the CSR model. While imputation overestimated selection for stress tolerance, field data indicated a greater diversity of strategies, with a greater presence of competitive species. The discrepancies point to limitations in the exclusive use of imputed data in local assessments of functional diversity, highlighting the need to integrate empirical collections and improvements in imputation methods for applications in environmental management and restoration.

In vivo and in vitro toxicokinetics including metabolism, isozyme mapping, and monoamine oxidase inhibition of three (2-aminopropyl)benzo[b]thiophene (APBT) psychedelics - Lea Wagmann; Simon D. Brandt; Pierce V. Kavanagh; Markus R. Meyer (Toxicology, 2026)

CSR ecological strategies explain plant species dominance in the Gandoman wetland, Iran - Shahrbanoo Rahmani; Zeinab Jafarian; Ataollah Ebrahimi; Barat Mojaradi; Simon Pierce (Plant Ecology, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

In vitro toxicokinetics and metabolic profiling of methoxycathinones and methylthiocathinones using human liver systems and hyphenated mass spectrometry - Matthias D. Kroesen; Tanja M. Gampfer; Lea Wagmann; Pierce V. Kavanagh; Simon D. Brandt; Markus R. Meyer (Archives of Toxicology, 2026)
Ring-substituted synthetic cathinones represent a major subgroup within new psychoactive substances. This study investigated the in vitro toxicokinetics of the three 4-methoxy-substituted representatives 4MeO-NE-BP (4’-methoxy- N -ethylbutyrophenone), 4MeO-αP-BP (4’-methoxy-α-pyrrolidinobutyrophenone), and 4MeO-αP-VP (4’-methoxy-α-pyrrolidinovalerophenone) and the three related novel 4-methylthio analogs 4MeS-NE-BP (4’-methylthio- N -ethylbutyrophenone), 4MeS-αP-BP (4’-methylthio-α-pyrrolidinobutyrophenone), and 4MeS-αMor-PrP (4’-methylthio-2-morpholinopropiophenone). This included plasma protein binding (PPB), phase I and phase II metabolism in pooled human liver S9 fraction (pHLS9) and HepaRG cells, and monooxygenases activity. Methoxycathinones exhibited lower PPB (~ 40–60%) compared to methylthiocathinones (~ 85%). Predominant phase I metabolic reactions included O -/ S -demethylation and hydroxylation, with additional transformations such as N -dealkylation, N -oxidation, and oxo reduction. Phase II conjugation reactions, such as glucuronidation and sulfation, were observed post-demethylation. Overall, 42 and 45 metabolites were identified in pHLS9 and HepaRG systems, respectively, with metabolite number increasing alongside alkyl chain length and heterocyclic substitution. All compounds were substrates for multiple monooxygenases, suggesting a low risk for drug–drug interactions. Based on metabolic stability and abundance, parent compounds and O -/ S -desmethyl and hydroxylated metabolites might be proposed as urinary screening targets in clinical and forensic toxicology, as well as doping control settings.

Whale shark residency and small-scale movements around oil and gas platforms in Qatar - Steffen S. Bach; David P. Robinson; Mohammed Y. Al Jaidah; Simon J. Pierce; Prasad Thoppil; Christoph A. Rohner (Frontiers in Marine Science, 2025)
Whale sharks seasonally aggregate near oil and gas platforms in Qatar to feed on fish spawn, creating one of the world’s largest aggregations of the species. We used passive acoustic telemetry to examine their fine-scale movements, residency, and seasonality and investigate whether the platforms influence their space use in this area. Tags had a mean retention of 161 ± 186 days (standard deviation, SD) and 32 of the 117 tags were recorded in multiple years in the acoustic array (21 stations). Most detections were recorded from May to September, confirming that this whale shark aggregation is seasonal. Whale sharks stayed up to 77 consecutive days in the array (mean = 16 ± 12.51 days) and had a mean residency index R max of 0.31. Although most detections (65%) were made at a single receiver located near a platform, here designated P1, an ‘open water’ receiver near this location also had a high proportion of total detections (8.5%). Receivers at other platforms, located away from this specific site, had relatively few detections. The distance from P1, identified as the center of the aggregation, was the main explanatory variable in a GAM. Whale shark aggregations were routinely observed feeding on tuna spawn at the surface at this location, with the eggs (and hence whale sharks) moving with the current through the day, and moving through the array as they did so. Whale sharks then swam against the current in the late afternoon and at night to relocate back to near the presumed tuna spawning site, close to P1, again in the early morning. Rather than being generally associated with platforms, whale sharks were clearly associated with a specific feeding location close to P1. Our results highlight the importance of this small feeding area for whale sharks, which face a high threat level in the region.

Movements and habitat use of reef manta rays around the Mozambique Channel Island of Mayotte, Southwestern Indian Ocean - Christoph A. Rohner; Stephanie K. Venables; Anna M. Knochel; Joshua M. Rambahiniarison; Vyctoria Marillac; Clémentine Cardon; Naomi Scholten; Simon J. Pierce; Jeremy J. Kiszka (Environmental Biology of Fishes, 2025)

Correction to: Persistent declines in sightings of manta and devil rays (mobulidae) at a global hotspot in southern mozambique - Stephanie K. Venables; Christoph A. Rohner; Anna L. Flam; Simon J. Pierce; Andrea D. Marshall (Environmental Biology of Fishes, 2025)

Persistent declines in sightings of manta and devil rays (Mobulidae) at a global hotspot in southern Mozambique - Stephanie K. Venables; Christoph A. Rohner; Anna L. Flam; Simon J. Pierce; Andrea D. Marshall (Environmental Biology of Fishes, 2025)
Mobulid rays are among the most vulnerable of chondrichthyans to overexploitation by fisheries due to their low population growth rates. In locations where catch data are lacking, long-term sightings data can provide valuable insight to infer population trends and status. We recorded underwater sighting data of reef manta rays ( Mobula alfredi ), oceanic manta rays ( M. birostris ), and shorthorned pygmy devil rays ( M. kuhlii ) between 2003 and 2023 in the waters off Praia do Tofo in the Inhambane Province, southern Mozambique, one of the major global hotspots for these rays. We modelled sightings data using a hierarchical generalised linear mixed model framework to account for a suite of environmental variables when examining temporal trends. Raw trend models including only ‘year’ as a predictor showed a 99% decline in sightings of reef manta rays, a 92.5% decline in oceanic manta ray sightings, and an 81.3% decline in devil ray sightings over the 20-year study period. The declining trends persisted for reef and oceanic manta rays once a suite of temporal and environmental variables were accounted for, indicating that the declines were driven by external factors not tested in the models. For shorthorned pygmy devil rays, models that incorporated environmental variables did not retain year as a significant predictor and showed a reduced overall decline in sightings of 36.5%. This indicates that the tested predictors were responsible for approximately half of the observed decline. Anthropogenic factors, particularly fisheries mortality, are likely to have played a significant role in the declining sightings of these three Threatened species. Improved conservation and management measures at a national and international level are critical to prevent further declines, which may otherwise lead to localised extinction.

Occurrence of mobulid rays in Northwest Madagascar - Stella Diamant; Caterina Bosio; Joshua Rambahiniarison; Chris Scarffe; Michel Strogoff; Jeremy J. Kiszka; Rhett Bennett; Tanguy Guillemain d’Echon; Elina Sourisseau; Léonce C. M. Fidiarisandratra; Salvatore Cerchio; Stephanie Venables; et al. (Environmental Biology of Fishes, 2025)
The waters around Nosy Be in northwest Madagascar are well-known for the occurrence of large planktivores, such as whale sharks ( Rhincodon typus ) and Omura’s whales ( Balaenoptera omurai ). Between 2016 and 2022, sighting data on mobulid rays were opportunistically collected during tourism activities. Additional sources, including citizen science submissions, tourism operator reports, and social media records, were used to compile sightings of three mobulid ray species. A total of 255 encounters were documented, with Mobula mobular ( n = 165) being the most common, followed by M. birostris ( n = 60) and M. kuhlii ( n = 30). Notably, the absence of confirmed M. alfredi records since 2015 suggests a potential local decline. This study highlights Nosy Be as a habitat for mobulid rays and emphasises the necessity for further species monitoring, ongoing identification of potential threats, and management initiatives aiming at reducing mortality from gillnet fishing.

Functional ecology of plant communities as a guide for vegetation management - Michele Dalle Fratte; Rossano Bolpagni; Simon Pierce; Bruno E.L. Cerabolini (Flora, 2025)

Effects of climate warming on energetics and habitat of the world's largest marine ectotherm - Samantha D. Reynolds; Craig E. Franklin; Bradley M. Norman; Anthony J. Richardson; Jason D. Everett; David S. Schoeman; Craig R. White; Christopher L. Lawson; Simon J. Pierce; Christoph A. Rohner; Steffen S. Bach; Francesco G. Comezzi; et al. (Science of The Total Environment, 2024)

Linking plant nitrogen use efficiency with single traits, ecological strategies and phylogeny in a temperate steppe - Cong Ding; Simon Pierce; Guo-Jiao Yang; Yan-Yu Hu; Zhi-Wei Zhang; Xiao-Tao Lü (Plant and Soil, 2024)

Best practices, errors, and perspectives of half a century of plant translocation in Italy - Martina D'Agostino; Luigi Cao Pinna; Marta Carboni; Silvia Assini; Gianluigi Bacchetta; Fabrizio Bartolucci; Lisa Brancaleoni; Fabrizio Buldrini; Angelino Carta; Bruno Cerabolini; Roberta Maria Ceriani; Umberto Clementi; et al. (Conservation Biology, 2024)
Conservation translocations are becoming common conservation practice, so there is an increasing need to understand the drivers of plant translocation performance through reviews of cases at global and regional levels. The establishment of the Italian Database of Plant Translocation (IDPlanT) provides the opportunity to review the techniques used in 186 plant translocation cases performed in the last 50 years in the heart of the Mediterranean Biodiversity Hotspot. We described techniques and information available in IDPlanT and used these data to identify drivers of translocation outcomes. We tested the effect of 15 variables on survival of translocated propagules as of the last monitoring date with binomial logistic mixed‐effect models. Eleven variables significantly affected survival of transplants: life form, site protection, material source, number of source populations, propagation methods, propagule life stage, planting methods, habitat suitability assessment, site preparation, aftercare, and costs. The integration of vegetation studies in the selection of suitable planting sites significantly increased the success of translocation efforts. Although posttranslocation watering had a generally positive effect on translocation outcome, other aftercare techniques did not always increase transplant survival. Finally, we found that how funds were spent appeared to be more important than the actual amount spent. Plant translocations in Italy and in the Mediterranean area should account for the complexity of speciation, gene flow, and plant migrations that has led to local adaptations and has important implications for the choice and constitution of source material.

Identifying priority sites for whale shark ship collision management globally - Freya C. Womersley; Christoph A. Rohner; Kátya Abrantes; Pedro Afonso; Shin Arunrugstichai; Steffen S. Bach; Shir Bar; Adi Barash; Peter Barnes; Adam Barnett; Ginevra Boldrocchi; Noemie Buffat; et al. (Science of The Total Environment, 2024)

Glomalin mediation of plant functional traits unveiled in an extreme ecosystem - Carla Rago; Daniel Negreiros; Yumi Oki; Dario C. Paiva; Vanessa M. Gomes; Simon Pierce; G. Wilson Fernandes (Flora, 2023)

Response of cetaceans to fluctuations of pelagic fish stocks and environmental conditions within the Celtic Sea ecosystem - Andrea Fariñas-Bermejo; Simon Berrow; Michaël Gras; Ciaran O’Donnell; Vasilis Valavanis; Dave Wall; Graham J. Pierce (Frontiers in Marine Science, 2023)
Inshore waters off the south coast of Ireland are an important foraging area for a range of cetacean species. Some of the main prey species of these cetaceans are herring and sprat, two economically valuable fish species in the region. The Celtic Sea herring stock suffered a marked decline in 2013. The present study aimed to investigate potential changes in the ecosystem associated to the herring decline and to determine the potential impacts on predators. Here we analyzed sightings information of common dolphins, fin, minke, humpback and unidentified whale species, acoustic data of herring and sprat, and a range of environmental variables mainly derived from satellites. Firstly, we characterized spatio-temporal patterns in the relative abundance of predator and prey species, and environmental variables, and compared periods before and since the herring decline. Since the 2013 herring decline, (i) the herring stock has mainly concentrated in south-eastern coastal waters and southern offshore Irish waters, (ii) sprat density has increased, (iii) chlorophyll concentration has decreased, (iv) sea surface temperature has risen, and (v) the euphotic layer has extended deeper. Secondly, we modelled the effects of prey density and environmental conditions on the relative abundance and distribution of cetaceans, as well as the effects of environmental conditions on prey density, between 2005-2018 by applying Hurdle Generalized Additive Models. The models for herring and sprat support the idea that these species have different environmental relationships, for example herring tended to be found in shallower waters than was the case for sprat. The presence and relative abundance of common dolphins were significantly affected by both environmental conditions and herring density, whereas whale species presence and relative abundance were found to be correlated with sea surface temperature and prey density. The model results suggest differences in prey choice among whale species. Understanding the dynamic relationships between predators, prey and the environment is important to inform an ecosystem-based approach to fisheries management.

Distribution of the reef manta ray Mobula alfredi and the oceanic manta ray Mobula birostris in the Philippines: a collaborative effort for conservation - Joshua Rambahiniarison; Ariana Agustines; Konstantinos Alexopoulos; Gonzalo Araujo; Asia O. Armstrong; Shannon Arnold; Aldrin Barruga; Titus Cañete; Segundo Conales; Kymry Delijero; Nonie P. Enolva; Anna L. Flam; et al. (Journal of Fish Biology, 2023)
Little is known about manta ray population size, structure and connectivity in the Philippines. In collaboration with dive operators, non‐governmental organizations and authorities, sightings of manta rays were collated into a single national database. Using in‐water photographs and videos gathered through citizen science and dedicated research efforts, this study compiled sightings between 2004 and 2020, showing 22 separate sites throughout the archipelago with manta rays present. A total of 392 individual reef manta rays ( Mobula alfredi ) and 107 oceanic manta rays ( Mobula birostris ) were identified from the collected footage. Four specific sites in the provinces of Masbate and Palawan together hosted 89% of all identified individuals and accounted for 95% of sightings, highlighting these areas are key aggregation sites. This study also reports the movements of M. birostris within the Philippines, based on photo‐identification of three individuals moving 150 km between Cebu and Masbate. Despite the growing number of recreational divers in Daanbantayan and San Jacinto, an 80% decline in M. birostris sightings was observed at these sites. To ensure effective future conservation, it is recommended that efforts focus on the identification and protection of manta ray hotspots and migratory corridors, the creation of a sustainable tourism framework and, most important, the implementation of mitigation strategies to reduce fisheries interactions.

The leaf anatomical trade-offs associated with plant ecological strategy variation - Simon Pierce; Dario Maffi; Franco Faoro; Bruno E. L. Cerabolini; Alberto Spada (Plant Ecology, 2022)
Plant functioning depends on variation in resource economics traits (acquisition vs. conservation) and the size of plants and their parts (the ‘global spectrum of plant form and function’). The anatomical basis of single traits (e.g., leaf mass per area; LMA) is generally understood, but little is known regarding the relationship between anatomical trade-offs and ecological strategies (representing integrated suites of traits). We hypothesised correlations between the relative extent of leaf tissue types and Grime’s Competitor Stress-tolerator Ruderal (CSR) strategies, principally a trade-off between structural (mechanical/fibro-vascular) vs. photosynthetic (chlorenchyma and intercellular airspace; ICAS) tissues, for ecologically contrasting herbaceous angiosperms in northern Italy. Specifically, that in the lamina portion, the trade-off represents the economics spectrum (S-R selection), but in the midvein portion, it reflects the mechanical constraints inherent to supporting large leaves (i.e., varies with C-selection). We used microscopy and image analysis to determine the relative cross-sectional area of tissues from transverse leaf sections (lamina and midvein portions) of angiosperms of contrasting CSR strategies. Principal components analysis (PCA) determined that the main trade-off (PCA1) was between mechanical/fibro-vascular tissues vs. ICAS/epidermis/chlorenchyma, but that this was associated with the economics spectrum (R- to S-selection) in the lamina, and with size (C-selection) for the midvein. A secondary trade-off in both lamina and midvein portions involved ICAS (i.e., the internal gas diffusion pathway) vs. chlorenchyma/epidermis (light capture), associated with S- to R-selection, respectively. Our results confirm the expectation that ecological strategy variation has a basis in underlying trade-offs between tissues with contrasting metabolic/architectural (i.e., economics/size-related) roles.

Citizen science reveals the population structure and seasonal presence of whale sharks in the Gulf of Thailand - Kirsty Magson; Emily Monacella; Chad Scott; Noémie Buffat; Sirachai Arunrugstichai; Metavee Chuangcharoendee; Simon J. Pierce; Jason Holmberg; Gonzalo Araujo (Journal of Fish Biology, 2022)
The whale shark Rhincodon typus is a broadly distributed and highly mobile planktivorous shark species. The sharks form predictable aggregations in many areas, providing the opportunity for cost‐effective scientific monitoring through divers and other marine resource users. Sightings of individuals outside of these aggregate zones elsewhere in their range are typically rare. We used a citizen science‐based approach to shed light on occurrence and seasonality in the waters around Koh Tao, Thailand and neighbouring islands in the Gulf of Thailand. Although there is a paucity of quantitative data, anecdotal reports suggest substantial declines in sightings in the early 2000s. We identified a total of 178 individual whale sharks (from 249 sightings) between 2004 and 2019, with most of these (84%) from the 2015–2019 time period due to an increase in sighting reports facilitated by social media and direct marketing. Size estimates were reported for 102 of the sightings, with a range of 2–6 m and mean of 3.7 m overall. Sex was reported for 27% of sightings, with a 2:1 female‐to‐male ratio. Modified maximum likelihood methods suggest whale sharks are transient to Koh Tao and surrounding areas, with whale shark sightings following the regional monsoon cycle. One international resighting was obtained from Malaysian waters (~700 km away). Encouraging citizen science participation is particularly useful in data‐poor regions like the Gulf of Thailand, despite limitations in size and sex estimation reliability, which can play an important complementary role in dedicated research programs.

Improving sightings-derived residency estimation for whale shark aggregations: A novel metric applied to a global data set - Gonzalo Araujo; Ariana Agustines; Steffen S. Bach; Jesse E. M. Cochran; Emilio de la Parra-Galván; Rafael de la Parra-Venegas; Stella Diamant; Alistair Dove; Steve Fox; Rachel T. Graham; Sofia M. Green; Jonathan R. Green; et al. (Frontiers in Marine Science, 2022)
The world’s largest extant fish, the whale shark Rhincodon typus , is one of the most-studied species of sharks globally. The discovery of predictable aggregation sites where these animals gather seasonally or are sighted year-round – most of which are coastal and juvenile-dominated – has allowed for a rapid expansion of research on this species. The most common method for studying whale sharks at these sites is photographic identification (photo-ID). This technique allows for long-term individual-based data to be collected which can, in turn, be used to evaluate population structure, build population models, identify long-distance movements, and assess philopatry and other population dynamics. Lagged identification rate (LIR) models have fewer underlying assumptions than more traditional capture mark recapture approaches, making them more broadly applicable to marine taxa, especially far-ranging megafauna species like whale sharks. However, the increased flexibility comes at a cost. Parameter estimations based on LIR can be difficult to interpret and may not be comparable between areas with different sampling regimes. Using a unique data-set from the Philippines with ~8 years of nearly continuous survey effort, we were able to derive a metric for converting LIR residency estimates into more intuitive days-per-year units. We applied this metric to 25 different sites allowing for the first quantitatively-meaningful comparison of sightings-derived residence among the world’s whale shark aggregations. We validated these results against the only three published acoustic residence metrics (falling within the ranges established by these earlier works in all cases). The results were then used to understand residency behaviours exhibited by the sharks at each site. The adjusted residency metric is an improvement to LIR-based population modelling, already one of the most widely used tools for describing whale shark aggregations. The standardised methods presented here can serve as a valuable tool for assessing residency patterns of whale sharks, which is crucial for tailored conservation action, and can cautiously be tested in other taxa.

Life at the continental–marine interface: palaeoenvironments and biota of the Alcobaça Formation (Late Jurassic, Central Portugal), with a formal definition of the unit appended - Franz T. Fürsich; Simon Schneider; Winfried Werner; Berta Lopez-Mir; Colm S. Pierce (Palaeobiodiversity and Palaeoenvironments, 2022)
The Kimmeridgian Alcobaça Formation of the Lusitanian Basin forms a mixed carbonate–siliciclastic unit between basinal deposits of the Abadia Formation, and fluvial–terrestrial strata of the Lourinhã Formation. This study presents >2.5 km of detailed logs of nine outcrop sections of the Alcobaça Formation in its type region. Eight of these sections encircle the Caldas da Rainha Diapir, which was a prominent, emergent, passive salt diapir during the time of deposition. Palaeoenvironments of the unit form a complex mosaic of low- to high-energy, carbonate- or siliciclastic-dominated shallow shelf settings; coastal embayments and lagoons; and coastal plains with rivers, lakes and playas. In the strata, abundant microfauna is often joined by a rich macrofauna, usually dominated by bivalves. Locally, corals, calcareous sponges or oysters form meadows or patch reefs. These autochthonous to parautochthonous remnants of former communities are assigned to 35 benthic macrofaunal associations. The integration of palaeoecological analysis of these associations with microfaunal and sedimentological data provides constraint on their salinity ranges, which range from slightly hypersaline to freshwater. Frequent temporal and spatial salinity fluctuations are attributed to variations in relative sea-level, salt tectonics or climate. The NNE-trending Caldas da Rainha Diapir induced pronounced facies differentiation. Predominantly, non-marine siliciclastic facies in the northwest and carbonate to siliciclastic, marine to brackish facies in the southwest are contrasted by shallow-marine carbonate facies east of the diapir. Comprehensive exposure and well-preserved fossils make the Alcobaça Formation an excellent showcase to demonstrate how biofacies analysis can help to disentangle the interplay of climate changes, sea-level fluctuations and salt tectonics. Based on the improved characterisation of the unit, the Alcobaça Formation is formally defined, and seven members are established.

Endemism in recently diverged angiosperms is associated with polyploidy - Sara Villa; Matteo Montagna; Simon Pierce (Plant Ecology, 2022)
Endemic (range restricted or precinctive) plant species are frequently observed to exhibit polyploidy (chromosome set duplication), which can drive shifts in ecology for angiosperms, but whether endemism is generally associated with polyploidy throughout the flowering plants has not been determined. We tested the hypothesis that polyploidy is more frequent and more pronounced (higher evident ploidy levels) for recently evolved endemic angiosperms. Chromosome count data, molecular dating and distribution for 4210 species (representing all major clades of angiosperms and including the largest families) were mined from literature-based databases. Upper boundary regression was used to investigate the relationship between the maximum number of chromosomes and time since taxon divergence, across clades and separately for families, comparing endemic with non-endemic species. A significant negative exponential relationship between maximum number of chromosomes and taxon age was evident across angiosperms ( R 2 adj = 0.48 for all species, R 2 adj = 0.49 for endemics; R 2 adj = 0.44 for non-endemics; p always < 0.0001), recent endemics demonstrating greater maximum chromosome numbers ( y intercept = 164 cf. 111) declining more rapidly with taxon age (decay constant = 0.12, cf. 0.04) with respect to non-endemics. The majority of families exhibited this relationship, with a steeper regression slope for endemic Campanulaceae, Asteraceae, Fabaceae, Poaceae, Caryophyllaceae and Rosaceae, cf. non-endemics. Chromosome set duplication is more frequent and extensive in recent angiosperms, particularly young endemics, supporting the hypothesis of recent polyploidy as a key explanation of range restriction. However, as young endemics may also be diploid, polyploidy is not an exclusive driver of endemism.

IDPlanT: the Italian database of plant translocation - Thomas Abeli; Martina D’Agostino; Simone Orsenigo; Fabrizio Bartolucci; Rita Accogli; Giulia Albani Rocchetti; Claudia Alessandrelli; Arianna Amadori; Filippo Amato; Claudia Angiolini; Silvia Assini; Gianluigi Bacchetta; et al. (Plant Biosystems, 2021)

Movement ecology of black marlin Istiompax indica in the Western Indian Ocean - Christoph A. Rohner; Roy Bealey; Bernerd M. Fulanda; Jason D. Everett; Anthony J. Richardson; Simon J. Pierce (Journal of Fish Biology, 2021)
The black marlin Istiompax indica is an apex marine predator and is susceptible to overfishing. The movement ecology of the species remains poorly known, particularly within the Indian Ocean, which has hampered assessment of their conservation status and fisheries management requirements. Here, we used pop‐up archival satellite tags to track I. indica movement and examine their dispersal. Forty‐nine tags were deployed off Kenya during both the north‐east (November–April) and south‐west (August–September) monsoon seasons, providing locations from every month of the year. Individual I. indica were highly mobile and track distance correlated with the duration of tag attachment. Mean track duration was 38 days and mean track distance was >1800 km. Individuals dispersed in several directions: north‐east into Somalian waters and up to northern Oman, east towards the Seychelles, and south into the Mozambique Channel. Their core habitat shifted seasonally and overlapped with areas of high productivity off Kenya, Somalia and Oman during the first half of the year. A second annual aggregation off the Kenyan coast, during August and September, did not coincide with high chlorophyll‐ a (chl‐ a ) concentrations or thermal fronts, and the drivers of the species' presence and movement from this second aggregation was unclear. We tested their habitat preferences by comparing environmental conditions at track locations to the conditions at locations along simulated tracks based on the empirical data. Observed I. indica preferred cooler water with higher chl‐ a concentrations and stayed closer to the coast than simulated tracks. The rapid and extensive dispersal of I. indica from Kenya suggests that there is likely a single stock in the Western Indian Ocean, with individuals swimming between areas of high commercial catches off northern Somalia and Oman, and artisanal and recreational fisheries catches throughout East Africa and Mozambique.

Functional biogeography of Neotropical moist forests: Trait–climate relationships and assembly patterns of tree communities - Bruno X. Pinho; Marcelo Tabarelli; Cajo J. F. ter Braak; S. Joseph Wright; Víctor Arroyo‐Rodríguez; Maíra Benchimol; Bettina M. J. Engelbrecht; Simon Pierce; Peter Hietz; Bráulio A. Santos; Carlos A. Peres; Sandra C. Müller; et al. (Global Ecology and Biogeography, 2021)
Aim Here we examine the functional profile of regional tree species pools across the latitudinal distribution of Neotropical moist forests, and test trait–climate relationships among local communities. We expected opportunistic strategies (acquisitive traits, small seeds) to be overrepresented in species pools further from the equator, but also in terms of abundance in local communities in currently wetter, warmer and more seasonal climates. Location Neotropics. Time period Recent. Major taxa studied Trees. Methods We obtained abundance data from 471 plots across nine Neotropical regions, including c . 100,000 trees of 3,417 species, in addition to six functional traits. We compared occurrence‐based trait distributions among regional species pools, and evaluated single trait–climate relationships across local communities using community abundance‐weighted means (CWMs). Multivariate trait–climate relationships were assessed by a double‐constrained correspondence analysis that tests both how CWMs relate to climate and how species distributions, parameterized by niche centroids in climate space, relate to their traits. Results Regional species pools were undistinguished in functional terms, but opportunistic strategies dominated local communities further from the equator, particularly in the Northern Hemisphere. Climate explained up to 57% of the variation in CWM traits, with increasing prevalence of lower‐statured, light‐wooded and softer‐leaved species bearing smaller seeds in more seasonal, wetter and warmer climates. Species distributions were significantly but weakly related to functional traits. Main conclusions Neotropical moist forest regions share similar sets of functional strategies, from which local assembly processes, driven by current climatic conditions, select for species with different functional strategies. We can thus expect functional responses to climate change driven by changes in relative abundances of species already present regionally. Particularly, equatorial forests holding the most conservative traits and large seeds are likely to experience the most severe changes if climate change triggers the proliferation of opportunistic tree species.

Climatic and evolutionary contexts are required to infer plant life history strategies from functional traits at a global scale - Ruth Kelly; Kevin Healy; Madhur Anand; Maude E. A. Baudraz; Michael Bahn; Bruno E. L. Cerabolini; Johannes H. C. Cornelissen; John M. Dwyer; Andrew L. Jackson; Jens Kattge; Ülo Niinemets; Josep Penuelas; et al. (Ecology Letters, 2021)
Life history strategies are fundamental to the ecology and evolution of organisms and are important for understanding extinction risk and responses to global change. Using global datasets and a multiple response modelling framework we show that trait‐climate interactions are associated with life history strategies for a diverse range of plant species at the global scale. Our modelling framework informs our understanding of trade‐offs and positive correlations between elements of life history after accounting for environmental context and evolutionary and trait‐based constraints. Interactions between plant traits and climatic context were needed to explain variation in age at maturity, distribution of mortality across the lifespan and generation times of species. Mean age at maturity and the distribution of mortality across plants’ lifespan were under evolutionary constraints. These findings provide empirical support for the theoretical expectation that climatic context is key to understanding trait to life history relationships globally.

The psychoactive aminoalkylbenzofuran derivatives, 5-APB and 6-APB, mimic the effects of 3,4-methylenedioxyamphetamine (MDA) on monoamine transmission in male rats - Simon D. Brandt; Hailey M. Walters; John S. Partilla; Bruce E. Blough; Pierce V. Kavanagh; Michael H. Baumann (Psychopharmacology, 2020)

St. Helena: An Important Reproductive Habitat for Whale Sharks (Rhincodon typus) in the Central South Atlantic - Cameron T. Perry; Elizabeth Clingham; D. Harry Webb; Rafael de la Parra; Simon J. Pierce; Annalea Beard; LeeAnn Henry; Beth Taylor; Kenickie Andrews; Rhys Hobbs; Gonzalo Araujo; Alistair D. M. Dove (Frontiers in Marine Science, 2020)

Movement and habitat use of striped marlin Kajikia audax in the Western Indian Ocean - Christoph A. Rohner; Roy Bealey; Bernerd M. Fulanda; Simon J. Pierce (Journal of Fish Biology, 2020)
Striped marlin Kajikia audax are globally Near Threatened and their stock in the Indian Ocean was last assessed as “overfished and subject to overfishing”. Significant gaps in our understanding of their ecology remain, hampering the efforts of fisheries managers to ensure stock sustainability. There is a particular lack of fisheries‐independent data. Here we present the results from the first large‐scale satellite tracking study of K. audax in the Indian Ocean. We tagged 49 K. audax with pop‐up archival satellite‐linked tags off the Kenyan coast from 2015 to 2019. Individuals were highly mobile, covering horizontal distances of up to 9187 km over periods ranging up to 183 days, with a mean daily distance of ~48 km. Long‐distance movements were recorded to the east and north of East Africa, with the most distant tracks extending north to the Arabian Sea and east to near the Maldives. None of the K. audax swam south of East Africa. Kernel utilization distributions of fish locations demonstrated their shifting seasonal activity hotspots. Over the sport‐fishing season (and tagging period) in Kenya, from December to March, K. audax typically stayed off the East African coast. After March, the activity hotspot shifted north to a region close to the Horn of Africa and Socotra Island. Remotely sensed sea surface temperature and chlorophyll‐ a maps indicated that this seasonal movement could be driven by a shift in prey availability. Our results show the high mobility of K. audax in the Western Indian Ocean, and that individuals seasonally range between two major fishing areas.

No Place Like Home? High Residency and Predictable Seasonal Movement of Whale Sharks Off Tanzania - Christoph A. Rohner; Jesse E. M. Cochran; E. Fernando Cagua; Clare E. M. Prebble; Stephanie K. Venables; Michael L. Berumen; Baraka L. Kuguru; Jason Rubens; Juerg M. Brunnschweiler; Simon J. Pierce (Frontiers in Marine Science, 2020)

Community-level variation in plant functional traits and ecological strategies shapes habitat structure along succession gradients in alpine environment - Magda Zanzottera; Michele Dalle Fratte; Marco Caccianiga; Simon Pierce; Bruno E. L. Cerabolini (Community Ecology, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Plant–environment interactions through a functional traits perspective: a review of Italian studies - Stefano Chelli; Michela Marignani; Elena Barni; Alessandro Petraglia; Giacomo Puglielli; Camilla Wellstein; Alicia T. R. Acosta; Rossano Bolpagni; Luca Bragazza; Giandiego Campetella; Alessandro Chiarucci; Luisa Conti; et al. (Plant Biosystems, 2019)

Sex change in kiwifruit (Actinidia chinensis Planch.): a developmental framework for the bisexual to unisexual floral transition - Elisabetta Caporali; Raffaele Testolin; Simon Pierce; Alberto Spada (Plant Reproduction, 2019)

Contrasting Habitat Use and Population Dynamics of Reef Manta Rays Within the Nusa Penida Marine Protected Area, Indonesia - Elitza S. Germanov; Lars Bejder; Delphine B. H. Chabanne; Dharmadi Dharmadi; I. Gede Hendrawan; Andrea D. Marshall; Simon J. Pierce; Mike van Keulen; Neil R. Loneragan (Frontiers in Marine Science, 2019)

Domestic gardens play a dominant role in selecting alien species with adaptive strategies that facilitate naturalization - Wen‐Yong Guo; Mark van Kleunen; Simon Pierce; Wayne Dawson; Franz Essl; Holger Kreft; Noëlie Maurel; Jan Pergl; Hanno Seebens; Patrick Weigelt; Petr Pyšek (Global Ecology and Biogeography, 2019)
Aim Horticulture has been recognized as the main pathway of plant invasions worldwide. The selection of ornamental garden plants is not random, and certain plant characteristics related to adaptive plant strategies are preferred by horticulture and may promote invasion. We examined the direct and indirect interactions between horticultural use, species adaptive strategies (competitive (C), stress‐tolerant (S), and ruderal (R)), native range size and naturalization success. Location Global. Time period From 1492 to the present. Major taxa studied Vascular plants. Methods We compiled a dataset of 3,794 plant species including their C‐, S‐ and R‐scores, native range size, cultivation in botanic and domestic gardens and whether the species is naturalized in at least one region globally (naturalization incidence). For the 1,711 naturalized species, we also calculated naturalization extent, that is, the number of regions where the species has naturalized. We used phylogenetic path analysis to disentangle the direct and indirect effects of all variables on both naturalization incidence and extent, and the relationships between variables. Results Approximately 87 and 94% of the 1,711 naturalized species were cultivated in botanic or domestic gardens, respectively, compared to c . 55 and 50% of the 2,083 non‐naturalized species, respectively. We found a cascading structure among the examined variables: (a) species exhibiting C‐ or R‐selected strategies and having large native ranges tended to be cultivated in domestic and botanic gardens, became naturalized outside their native ranges and occupied more regions in their naturalized ranges; (b) C‐, S‐ and R‐scores also had indirect effects on naturalization success, which were mediated by horticultural use and native range size; and (c) cultivation in domestic gardens was the strongest factor examined that could explain plant species’ naturalization success. Main conclusions We show that horticulture is not only the major introduction pathway of alien plants, but also that in particular domestic gardens select species predisposed to invade and naturalize.

Differential biodiversity responses between kingdoms (plants, fungi, bacteria and metazoa) along an Alpine succession gradient - Matteo Montagna; Andrea Berruti; Valeria Bianciotto; Paola Cremonesi; Riccardo Giannico; Fausto Gusmeroli; Erica Lumini; Simon Pierce; Flavia Pizzi; Federica Turri; Gustavo Gandini (Molecular Ecology, 2018)
Biological diversities of multiple kingdoms potentially respond in similar ways to environmental changes. However, studies either compare details of microbial diversity across general vegetation or land use classes or relate details of plant community diversity with the extent of microbially governed soil processes, via physiological profiling. Here, we test the hypothesis of shared responses of plant and rhizosphere bacterial, fungal and metazoan biodiversities (especially across‐habitat β‐diversity patterns) along a disturbance gradient encompassing grazed to abandoned Alpine pasture, on acid soil in the European Central Alps. Rhizosphere biological diversity was inferred from eDNA fractions specific to bacteria, fungi and metazoans from contrasting plant habitats indicative of different disturbance levels. We found that soil β‐diversity patterns were weakly correlated with plant diversity measures and similarly ordinated along an evident edaphic (pH, C:N, assimilable P) and disturbance gradient but, contrary to our hypothesis, did not demonstrate the same diversity patterns. While plant communities were well separated along the disturbance gradient, correlating with fungal diversity, the majority of bacterial taxa were shared between disturbance levels (75% of bacteria were ubiquitous, cf . 29% plant species). Metazoa exhibited an intermediate response, with communities at the lowest levels of disturbance partially overlapping. Thus, plant and soil biological diversities were only loosely dependent and did not exhibit strictly linked environmental responses. This probably reflects the different spatial scales of organisms (and their habitats) and capacity to invest resources in persistent multicellular tissues, suggesting that vegetation responses to environmental change are unreliable indicators of below‐ground biodiversity responses.

The role of adaptive strategies in plant naturalization - Wen‐Yong Guo; Mark van Kleunen; Marten Winter; Patrick Weigelt; Anke Stein; Simon Pierce; Jan Pergl; Dietmar Moser; Noëlie Maurel; Bernd Lenzner; Holger Kreft; Franz Essl; et al. (Ecology Letters, 2018)
Determining the factors associated with the naturalization of alien species is a central theme in ecology. Here, we tested the usefulness of a metric for quantifying Grime's seminal concept of adaptive strategies – competitors, stress‐tolerators and ruderals ( CSR ) – to explain plant naturalizations worldwide. Using a global dataset of 3004 vascular plant species, and accounting for phylogenetic relatedness and species’ native biomes, we assessed the associations between calculated C‐, S‐ and R‐scores and naturalization success for species exhibiting different life forms. Across different plant life forms, C‐scores were positively and S‐scores negatively associated with both the probability of naturalization and the number of regions where the species has naturalized. R‐scores had positive effects on the probability of naturalization. These effects of the scores were, however, weak to absent for tree species. Our findings demonstrate the utility of CSR ‐score calculation to broadly represent, and potentially explain, the naturalization success of plant species.

Identifying population thresholds for flowering plant reproductive success: the marsh gentian (Gentiana pneumonanthe) as a flagship species of humid meadows and heathland - Simon Pierce; Alberto Spada; Elisabetta Caporali; Filippa Puglisi; Andrea Panzeri; Alessandra Luzzaro; Simona Cislaghi; Lia Mantegazza; Elisa Cardarelli; Massimo Labra; Andrea Galimberti; Roberta M. Ceriani (Biodiversity and Conservation, 2018)

iDNA at Sea: Recovery of Whale Shark (Rhincodon typus) Mitochondrial DNA Sequences from the Whale Shark Copepod (Pandarus rhincodonicus) Confirms Global Population Structure - Mark Meekan; Christopher M. Austin; Mun H. Tan; Nu-Wei V. Wei; Adam Miller; Simon J. Pierce; David Rowat; Guy Stevens; Tim K. Davies; Alessandro Ponzo; Han Ming Gan (Frontiers in Marine Science, 2017)

Spatial Distribution and Residency of Green and Loggerhead Sea Turtles Using Coastal Reef Habitats in Southern Mozambique - Jessica L. Williams; Simon J. Pierce; Chris A. Rohner; Mariana M. P. B. Fuentes; Mark Hamann (Frontiers in Marine Science, 2017)

Plant community attributes affect dry grassland orchid establishment - Antonio Slaviero; Silvia Del Vecchio; Simon Pierce; Edy Fantinato; Gabriella Buffa (Plant Ecology, 2016)

Prioritization of knowledge‐needs to achieve best practices for bottom trawling in relation to seabed habitats - Michel J Kaiser; Ray Hilborn; Simon Jennings; Ricky Amaroso; Michael Andersen; Kris Balliet; Eric Barratt; Odd A Bergstad; Stephen Bishop; Jodi L Bostrom; Catherine Boyd; Eduardo A Bruce; et al. (Fish and Fisheries, 2016)
Management and technical approaches that achieve a sustainable level of fish production while at the same time minimizing or limiting the wider ecological effects caused through fishing gear contact with the seabed might be considered to be ‘best practice’. To identify future knowledge‐needs that would help to support a transition towards the adoption of best practices for trawling, a prioritization exercise was undertaken with a group of 39 practitioners from the seafood industry and management, and 13 research scientists who have an active research interest in bottom‐trawl and dredge fisheries. A list of 108 knowledge‐needs related to trawl and dredge fisheries was developed in conjunction with an ‘expert task force’. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge‐need. The top 25 knowledge‐needs are presented, as scored separately by practitioners and scientists. There was considerable consistency in the priorities identified by these two groups. The top priority knowledge‐need to improve current understanding on the distribution and extent of different habitat types also reinforced the concomitant need for the provision and access to data on the spatial and temporal distribution of all forms of towed bottom‐fishing activities. Many of the other top 25 knowledge‐needs concerned the evaluation of different management approaches or implementation of different fishing practices, particularly those that explore trade‐offs between effects of bottom trawling on biodiversity and ecosystem services and the benefits of fish production as food.

Occurrence of demersal fishes in relation to near‐bottom oxygen levels within the C alifornia C urrent large marine ecosystem - Aimee A. Keller; Lorenzo Ciannelli; W. Waldo Wakefield; Victor Simon; John A. Barth; Stephen D. Pierce (Fisheries Oceanography, 2015)
Various ocean‐climate models driven by increased greenhouse gases and higher temperatures predict a decline in oceanic dissolved oxygen ( DO ) as a result of greater stratification, reduced ventilation below the thermocline, and decreased solubility at higher temperatures. Since spreading of low oxygen waters is underway and predicted to increase, understanding impacts on higher trophic levels is essential. Within the California Current System, shoaling of the oxygen minimum zone ( OMZ ) is expected to produce complex changes. Onshore movement of the OMZ could lead to habitat compression for species with higher oxygen requirements while allowing expansion of species tolerant of low bottom DO . As part of annual groundfish surveys, we sampled catch across a range of conditions from the upper to the lower limit of the OMZ and shoreward across the continental shelf of the US west coast. DO ranged from 0.02 to 4.25 mL L −1 with 642 stations (of 1020 sampled) experiencing hypoxic conditions in 2008–2010. Catch and species richness exhibited significant and positive relationships with near‐bottom oxygen concentration. The probability of occurrence was estimated for four species (spotted ratfish, petrale sole, greenstriped rockfish and Dover sole) using a binomial Generalized Additive Model. The models for each species included terms for position, day of the year, salinity, near‐bottom temperature and the interaction term between depth and near‐bottom DO . Spotted ratfish and petrale sole were sensitive to changes in near‐bottom oxygen, while greenstriped rockfish and Dover sole show no changes in probability of occurrence in relation to changes in oxygen concentration.

Pea seed extracts stimulate germination of the terrestrial orchid Ophrys apifera Huds. during a habitat restoration project - Simon Pierce; Valentina Guidi; Andrea Ferrario; Roberta M. Ceriani; Massimo Labra; Ilda Vagge; Bruno E. L. Cerabolini (Plant Biosystems, 2015)

How well do seed production traits correlate with leaf traits, whole-plant traits and plant ecological strategies? - Simon Pierce; Arianna Bottinelli; Ilaria Bassani; Roberta M. Ceriani; Bruno E. L. Cerabolini (Plant Ecology, 2014)

The intimacy between sexual traits and Grime’s CSR strategies for orchids coexisting in semi-natural calcareous grassland at the Olive Lawn - Simon Pierce; Ilda Vagge; Guido Brusa; Bruno E. L. Cerabolini (Plant Ecology, 2014)

Genetic structure of populations of whale sharks among ocean basins and evidence for their historic rise and recent decline - Thomas M. Vignaud; Jeffrey A. Maynard; Raphael Leblois; Mark G. Meekan; Ricardo Vázquez‐Juárez; Dení Ramírez‐Macías; Simon J. Pierce; David Rowat; Michael L. Berumen; Champak Beeravolu; Sandra Baksay; Serge Planes (Molecular Ecology, 2014)
This study presents genetic evidence that whale sharks, Rhincodon typus , are comprised of at least two populations that rarely mix and is the first to document a population expansion. Relatively high genetic structure is found when comparing sharks from the Gulf of Mexico with sharks from the Indo‐Pacific. If mixing occurs between the Indian and Atlantic Oceans, it is not sufficient to counter genetic drift. This suggests whale sharks are not all part of a single global metapopulation. The significant population expansion we found was indicated by both microsatellite and mitochondrial DNA . The expansion may have happened during the Holocene, when tropical species could expand their range due to sea‐level rise, eliminating dispersal barriers and increasing plankton productivity. However, the historic trend of population increase may have reversed recently. Declines in genetic diversity are found for 6 consecutive years at Ningaloo Reef in Australia. The declines in genetic diversity being seen now in Australia may be due to commercial‐scale harvesting of whale sharks and collision with boats in past decades in other countries in the Indo‐Pacific. The study findings have implications for models of population connectivity for whale sharks and advocate for continued focus on effective protection of the world's largest fish at multiple spatial scales.

A Framework for Quantitative Assessment of Impacts Related to Energy and Mineral Resource Development - Seth S. Haines; Jay E. Diffendorfer; Laurie Balistrieri; Byron Berger; Troy Cook; Don DeAngelis; Holly Doremus; Donald L. Gautier; Tanya Gallegos; Margot Gerritsen; Elisabeth Graffy; Sarah Hawkins; et al. (Natural Resources Research, 2014)

Quantification of the relationship between the environment and Fusarium head blight, Fusarium pathogen density, and mycotoxins in winter wheat in Europe - Alissa B. Kriss; Pierce A. Paul; Xiangming Xu; Paul Nicholson; Fiona M. Doohan; Laszlo Hornok; Alberto Rietini; Simon G. Edwards; Laurence V. Madden (European Journal of Plant Pathology, 2012)

Mining the plant–herbivore interface with a leafmining Drosophila of Arabidopsis - NOAH K. WHITEMAN; SIMON C. GROEN; DANIELA CHEVASCO; ASHLEY BEAR; NOOR BECKWITH; T. RYAN GREGORY; CARINE DENOUX; NICOLE MAMMARELLA; FREDERICK M. AUSUBEL; NAOMI E. PIERCE (Molecular Ecology, 2011)
Experimental infections of Arabidopsis thaliana ( Arabidopsis ) with genomically characterized plant pathogens such as Pseudomonas syringae have facilitated the dissection of canonical eukaryotic defence pathways and parasite virulence factors. Plants are also attacked by herbivorous insects, and the development of an ecologically relevant genetic model herbivore that feeds on Arabidopsis will enable the parallel dissection of host defence and reciprocal resistance pathways such as those involved in xenobiotic metabolism. An ideal candidate is Scaptomyza flava , a drosophilid fly whose leafmining larvae are true herbivores that can be found in nature feeding on Arabidopsis and other crucifers. Here, we describe the life cycle of S. flava on Arabidopsis and use multiple approaches to characterize the response of Arabidopsis to S. flava attack. Oviposition choice tests and growth performance assays on different Arabidopsis ecotypes, defence‐related mutants, and hormone and chitin‐treated plants revealed significant differences in host preference and variation in larval performance across Arabidopsis accessions. The jasmonate and glucosinolate pathways in Arabidopsis are important in mediating quantitative resistance against S. flava , and priming with jasmonate or chitin resulted in increased resistance. Expression of xenobiotic detoxification genes was reduced in S. flava larvae reared on Arabidopsis jasmonate signalling mutants and increased in plants pretreated with chitin. These results and future research directions are discussed in the context of developing a genetic model system to analyse insect–plant interactions.

Can CSR classification be generally applied outside Britain? - Bruno E. L. Cerabolini; Guido Brusa; Roberta M. Ceriani; Rossella De Andreis; Alessandra Luzzaro; Simon Pierce (Plant Ecology, 2010)

Species evenness affects ecosystem processes in situ via diversity in the adaptive strategies of dominant species - Bruno Cerabolini; Simon Pierce; Alessandra Luzzaro; Alessandro Ossola (Plant Ecology, 2010)

The survival strategy of the alpine endemic Primula glaucescens is fundamentally unchanged throughout its climate envelope despite superficial phenotypic variability - Roberta M. Ceriani; Simon Pierce; Bruno Cerabolini (Plant Ecology, 2009)

Quantifying Relative Extinction Risks and Targeting Intervention for the Orchid Flora of a Natural Park in the European Prealps - SIMON PIERCE; ROBERTA M. CERIANI; MAURO VILLA; BRUNO CERABOLINI (Conservation Biology, 2006)
Conservation currently relies largely on hindsight because demographic studies identify population decline after the event. Nevertheless, the degree of aggregation within a population is an “instantaneous” characteristic with the potential to identify populations presently at greatest risk of genetic impoverishment (via Allee effects and in‐breeding depression) and local decline. We sought to determine the relative extinction risk for sympatric orchid species throughout Monte Barro natural park (Lecco, Italy), based on an index of dispersion ( I ) calculated from the size and location of subpopulations (recorded with GPS and mapped with GIS). Three population dispersion types were identified: (1) highly aggregated and locally abundant (large subpopulations restricted to particular sites; e.g., Gymnadenia conopsea [L.] R.Br.; I= 54.5); (2) widespread and moderately aggregated (opportunistic throughout the elevational range of the mountain; e.g., Listera ovata[L.] R.Br.; I = 18.9); and (3) weakly aggregated and locally rare (small, highly diffuse subpopulations; e.g., endemic Ophrys benacensis [Reisigl] O. & E. Danesch & Ehrend.; I = 4.4). Type 1 populations are more likely to respond to in situ intervention, whereas type 2 are relatively invasive species for which conservation intervention is not necessary, and type 3 are rare species that are least likely to respond to habitat management, for which ex situ conservation and population reinforcement would be most appropriate. Although our methodology provides only a “snapshot” of aboveground patterns of population dispersion, it can help target the application of in situ and ex situ conservation activities proactively and is of particular utility for parks for which a rapid assessment of local extinction risks is needed.